2022
DOI: 10.3390/ijerph19063421
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of a Synbiotic Does Not Affect the Immune, Inflammatory, and Sympathovagal Parameters in Athletes and Sedentary Individuals: A Triple-Blinded, Randomized, Place-bo-Controlled Pilot Study

Abstract: This investigation aimed to identify the effect of a synbiotic in athletes and sedentary people, and their potential varying responses regarding the immune system, autonomic regulation and body composition. Twenty-seven participants were involved in the protocol: 14 sedentary and 13 semi-professional soccer players. Both groups were randomly divided into an experimental and control group. A synbiotic (Gasteel Plus®®, Heel España S.A.U.) comprising a blend of probiotic strains, including Bifidobacterium lactis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Five of the selected RCTs lasted 4 weeks (30 days) [21,[23][24][25][26], one RCT lasted 8 weeks [27], and three RCTs lasted from 11 to 12 weeks (90 days) [8,20,22]. Sticks, capsules, sachets, or fermented milk were consumed once or twice per day during the supplementation period.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of the selected RCTs lasted 4 weeks (30 days) [21,[23][24][25][26], one RCT lasted 8 weeks [27], and three RCTs lasted from 11 to 12 weeks (90 days) [8,20,22]. Sticks, capsules, sachets, or fermented milk were consumed once or twice per day during the supplementation period.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A study reported that the consumption of a symbiotic bacterium did not affect immuneand inflammation-related markers in athletes [25]. Pugh et al indicated that the IL-6, IL-8, and IL-10 levels were not significantly different before or after the race between the placebo and probiotic groups, although athletes self-reported lower incidence and severity of gastrointestinal tract symptoms [23].…”
Section: Overall Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…The general characteristics of the included studies are outlined in Table S4. Trials were published between 1996 and 2023, and were carried out in Asia, 12,27–31,77–81,84–229 Europe, 230–262 America,…”
Section: Resultsmentioning
confidence: 99%